The correlation between plasma cortisol levels and scores of psychological scales among patients with recurrent depressive disorder in Vietnam - Tuan Van Nguyen; Eric Hahn; Thi Minh Tam Ta; Thi Phuong Mai Nguyen; Hoa Thi Nguyen; Quynh Thi Pham; Duc Minh Nguyen; Thi Thuy Chuyen Dieu; Thi Phuong Thao Nguyen; Ngan Thi Vuong; Tung Son Vu (PLoS ONE, 2025)
Objectives We aimed to examine levels of plasma cortisol in the morning and evening before and after standardised treatment, and analyze the correlation between these levels and scores of psychological assessment scales among patients with recurrent depressive disorder (PRDD) in Vietnam. Methods From January 2020 to December 2021, a cross-sectional study was carried out at the National Institute of Mental Health in Bach Mai Hospital. After using a convenience sampling method, 109 consecutive patients met our criteria were recruited. We measured and analysed plasma cortisol levels in all participants at baseline (T0), two weeks after treatment (T1) and four weeks after treatment (T2). Spearman correlation was applied to assess the correlations between plasma cortisol at six different time and scores of six psychological assessment scales including HAM-D, HAM-A, BDI, SAS, DASS, and MMSE. Results Among 109 PRDD, the percentage of subjects had high cortisol levels decreased during hospital treatment. At admission (T0), these figures were 4.76% in the morning and 8% in the evening. After 4-week treatment (T2), these figures declined to 1.32% and 3.09%, respectively. At T0, the morning cortisol concentrations had a positive correlation with the mean scores of HAM-A (r = 0.257), BDI (r = 0.251), and SAS (r = 0.276) (p ≤ 0.05), whereas the evening cortisol concentrations in the evening had a positive correlation with the mean scores of BDI (r = 0.197), SAS (r = 0.206), and Depression subscale of DASS (r = 0.252) (p ≤ 0.05). At T2, we did not detect any correlation between morning or evening cortisol levels and six test scores. Conclusion The utilization of psychological measures for monitoring purposes can facilitate the assessment of alterations in cortisol levels among individuals experiencing recurrent depression, hence aiding in the treatment of depression in this population. Additional investigation using a more extensive sample size is required to furnish additional substantiation on this matter in Vietnam.